Determination of economic indicators in the context of corporate sustainability performance - Docekalova, Marie; Kocmanová, Alena; Koleňák, Jiří (Business: Theory and Practice, 2015)
This article is focused on determination of the most significant economic indicators influencing corporate sustainability performance. Corporate sustainability performance is a multidimensional concept based on the original idea of sustainable development, replacing the traditional understanding of corporate performance only as capital appreciation for owners (shareholders). Compared to the original concept of sustainable development which consists of environmental, social and economic performance, the so-called triple-bottom-line, it is broaden to the responsibilities and the impact of Corporate Governance on the corporate performance. The basic set of economic indicators has been constructed from a synthesis of resources developed by international organizations (Global Reporting Initiative, International Federation of Accountants) and research among manufacturing companies in the Czech Republic. The basic set of twenty-five key indicators is divided into seven groups: Costs, Investments, Economic Results, Asset & financial resources utilization, Suppliers reliability, Penalties and R&D expenses. Basic set of indicators was presented to 23 top-managers who quantified the potential effect of each indicator to the success and sustainability of their companies. Through the methods of descriptive statistics knowledge of the particularities of each indicator was obtained. Correlation analysis and factor analysis were applied in order to eliminate information duplicity and dimensionality reduction. The result is a reduction in the number of economic indicators, so that the loss of information on the influence of the original indicators on the corporate sustainability is minimized. Corporate sustainability indicators are a tool for measuring and managing progress towards sustainability goals and environmental, social and economic impacts.